Analisis Pengaruh Faktor Sosial Ekonomi, Pendapatan dan Harga Rokok Terhadap Konsumsi Rokok di Indonesia - Marianti, Annisa; Prayitno, Budi (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2020)
Indonesia is one of the tobacco producer countries in the world and ranks sixth out of the ten largest cigarette consuming countries in the world. Cigarettes kill more than five million people every year, and are projected to kill ten million people by 2020. Of that number 70% of victims come from developing countries including Indonesia. One of the government's efforts in controlling the negative impact of cigarette consumption is by setting cigarette excise prices. The government increases the cigarette excise price by 10.04 percent which is valid from January 1, 2018. Price elasticity, income, and socio-economic factors that influence consumer response are very important as a reference in determining cigarette consumption control policies. In this connection, this study aims to analyze the effect of socioeconomic factors, individual income, and cigarette prices on cigarette consumption in Indonesia. By using a simple linear regression model. The data used was obtained from IFLS-5 published by RAND (Research and Development Corporation). The results of this study found that socioeconomic factors, namely gender and age, individual income, and cigarette prices have no effect on cigarette consumption in Indonesia.